Measurement of the cross section of e + e − → Ξ − Ξ ¯ + $$ {e}^{+}{e}^{-}→ Ξ^{-}{\overline{Ξ}}^{+} $$ at center-of-mass energies between 3.510 and 4.843 GeV - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; X. C. Ai; R. Aliberti; A. Amoroso; M. R. An; Q. An; Y. Bai; O. Bakina; I. Balossino; et al. (Journal of High Energy Physics, 2023)
Abstract Using e + e − collision data corresponding to a total integrated luminosity of 12.9 fb −1 collected with the BESIII detector at the BEPCII collider, the exclusive Born cross sections and the effective form factors of the reaction e + e − → Ξ − Ξ ¯ + $$ {e}^{+}{e}^{-}→ Ξ^{-}{\overline{Ξ}}^{+} $$ are measured via the single baryon-tag method at 23 center-of-mass energies between 3.510 and 4.843 GeV. Evidence for the decay ψ 3770 → Ξ − Ξ ¯ + $$ ψ (3770)→ Ξ^{-}{\overline{Ξ}}^{+} $$ is observed with a significance of 4.5σ by analyzing the measured cross sections together with earlier BESIII results. For the other charmonium(-like) states ψ(4040), ψ(4160), Y(4230), Y(4360), ψ(4415), and Y(4660), no significant signal of their decay to Ξ − Ξ ¯ + $$ Ξ^{-}{\overline{Ξ}}^{+} $$ is found. For these states, upper limits of the products of the branching fraction and the electronic partial width at the 90% confidence level are provided.